Occurrence of arbovirus infections in two riverine populations in the municipality of Humaitá, Amazonas, Brazil - Jaqueline Carvalho de Oliveira Silva; Igor Rodrigo Ferreira Siqueira; Leormando Fortunato Dornelas; Cristhian Magalhães Ribeiro; João Pedro Berno Gomes; Iagor Wingenbah Guadagnin; Antonieta Relvas Pereira; Genimar Rebouças Julião; Juliana de Souza Almeida Aranha Camargo; Sergio Almeida Basano; Luís Marcelo Aranha Camargo (Revista da Sociedade Brasileira de Medicina Tropical, 2024)
ABSTRACT Background: The riverine communities of the Amazon comprise different social groups that inhabit the rural areas on the banks of rivers and lakes. Residents usually travel by river to rural and urban areas and are then exposed to urbanized diseases such as those caused by arbovirus infection. In Brazil, emerging diseases such as dengue, Zika, chikungunya, and those caused by infection with Oropouche and Mayaro viruses necessitate epidemiological surveillance. This study was aimed at determining the frequency of positivity for immunoglobulin (Ig)G and IgM antibodies against Zika, chikungunya, and dengue viruses and performing molecular analyses to detect viral RNA for the Zika, chikungunya, dengue virus, Oropouche, and Mayaro viruses, in the same serum samples obtained from riverside populations. Methods: This cross-sectional study was conducted in a riverside population in the Humaitá municipality of the Brazilian Amazon. More than 80% of the local population participated in this study. Entomological samples were collected to identify local mosquito vectors. Results: Analysis of 205 human serological samples revealed IgG antibodies against the dengue virus in 85 individuals. No molecular positivity was observed in human samples. Entomological analyses revealed 3,187 Diptera species, with Mansonia being the most frequent genus. Aedes aegypti and Aedes albopictus were not detected in the two collections. Conclusions: IgG antibodies against the dengue virus were highly prevalent, suggesting previous exposure. The absence of the arbovirus vectors Aedes aegypti and Aedes albopictus in the samples supports the hypothesis that the infections recorded likely occurred outside the riverside communities investigated.